Escuelas de Avanzada. Un proyecto educativo con incidencias significativas en comunicación - Valdízán Carrasco, Hernán (2007)
In this article we present interrelation between education and communication through the experience of the project Cutting-edge Schools, in one of its components, the principals as well as the design of standards for good management, professional development and self-assessment of management work. In the firs stage of the project five standards were designed; one of them is particularly referred to communication and on which principals were self-assessed and assumed achievement commitments.